Natural Disasters and Maternal-Neonatal Health Services: Systematic Review of Services Disruption and Recovery - Efa Nugroho; Budiyono; Yusniar Hanani Darundiati; Cahya Tri Purnami; Ayu Istiada (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Sudden-onset natural disasters rapidly disrupted essential maternal and neonatal health (MNH) services across the disaster cycle. This systematic review synthesized how such events affected the disruption and recovery of antenatal care (ANC), facility delivery, and emergency obstetric and neonatal care (EmONC), as well as postnatal/neonatal care, and identified the main health-system pathways involved. Searches of Scopus, ScienceDirect, and PubMed (November–December 2025) included English-language, open-access articles published between 2021 and 2026. Eligible quantitative, qualitative, and mixed-methods studies examined sudden-onset disasters and reported disruption and/or recovery of essential MNH services. Using PRISMA procedures, PEO-based criteria, and the MMAT 2018 quality appraisal, seven studies were included, primarily focusing on floods and cyclones in South Asia, Sub-Saharan Africa, and the Caribbean islands. Disasters generated acute shocks to service delivery, workforce, supplies, referral and transport, and information and coordination, leading to declines in ANC, facility delivery/EmONC, and PNC/neonatal care. Recovery ranged from return to near baseline within about three months to prolonged and uneven restoration, with poorer, marginalized, and remote groups being consistently more affected. The findings highlighted predictable but inequitable system pathways, supporting the integration of MISP-aligned preparedness, protection of ANC/PNC platforms, securing EmONC referral and transport, strengthening supply chains, and improving routine information systems to sustain continuity and accelerate recovery.